2015
DOI: 10.3136/fstr.21.309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Xanthan Gum on Improvement of Bread Height and Specific Volume upon Baking with Frozen and Thawed Dough

Abstract: Wheat flour was preliminarily mixed with 5% polysaccharides (locust bean gum, guar gum, xanthan gum, tamarind seed gum, native gellan gum, dextrin, LM pectin, fermented cellulose CMC, konjac glucomannan, HM pectin, κ-carrageenan, ι-carrageenan, and λ-carrageenan), and then mixed with water, salt, sugar, and yeast,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…When GG, XG or TSG (5% f.b.) were added to frozen dough, higher specific volumes were obtained in comparison with control bread (Morimoto, Tabara, & Seguchi, 2015). TG (1% f.b.)…”
Section: Hydrocolloids Used In Bake Off Technologiesmentioning
confidence: 99%
“…When GG, XG or TSG (5% f.b.) were added to frozen dough, higher specific volumes were obtained in comparison with control bread (Morimoto, Tabara, & Seguchi, 2015). TG (1% f.b.)…”
Section: Hydrocolloids Used In Bake Off Technologiesmentioning
confidence: 99%
“…Davidou et al (1996) reported that xanthan gum decreased the rigidity of bread as determined by dynamic mechanical measurements. Furthermore, xanthan gum improves the quality of frozen dough and par-baked bread applications by increasing water retention, improving freezethaw stability, and increasing final loaf volume (Mandala, Kapetanakou, & Kostaropoulos, 2008;Morimoto, Tabara, & Seguchi, 2015). Xanthan gum has received increased attention in recent years for its potential to improve gluten-free baking applications (Peressini, Pin, & Sensidoni, 2011;Sciarini, Ribotta, Leon, & Perez, 2010).…”
mentioning
confidence: 99%
“…The loss of the specific volume of dough due to the freezing stage is critical for GF bread because the GF dough loses its gas retention capacity in the proofing and baking processes (Mezaize et al ., ). Nevertheless, the quality characteristics of GF products using GF frozen dough are not affected when hydrocolloids are used, especially guar gum (Mezaize et al ., ; Morimoto et al ., ). Moreover, this study shows that the specific volume and height of GF cheese bread were improved by adding guar gum in GF cheese dough.…”
Section: Resultsmentioning
confidence: 97%